COMBINED ABDOMINAL HYSTERECTOMY, CHOLECYSTECTOMY AND APPENDICECTOMY: A STUDY OF 25 CASES IN ABBOTTABAD - Griffin, Samson; Abbassi, Nasreen; Parveen, Zahida; Zafar, Arshad; Ali, Johar (Journal of Ayub Medical College Abbottabad, 2006)
Background: Gallstone disease is common in women. Many patients undergoing abdominal ultrasound for gynaecological diseases are found to have gallstones. This study was done to see the results of combined abdominal hysterectomy, mini-cholecystectomy and appendicectomy in a set up lacking facilities of laparoscopic surgery. Methods: This prospective study was conducted in Ayub Teaching Hospital, Iltaf Hospital and Shahina Jamil Trust Hospital of Abbottabad from August 1998 to July 2004. All patients undergoing combined abdominal hysterectomy and minicholecystectomy were exclusively studied with reference to following variables. Age, Weight, Parity, Co-morbid conditions, peri-operative and post-operative complications, blood transfusion, hospital stay and mean extra time for mini-cholecystectomy and appendicectomy after abdominal hysterectomy. Results: There were 25 patients in the study group. The ages ranged from 35-50 years. Mean weight was 65 Kg. There were no operative complications. Mild postoperative complications occurred in 7(28%) patients. Mean extra time for cholecystectomy was 25 minutes. Mean hospital stay was 9 days. Conclusions: In selected women, combined abdominal hysterectomy, cholecystectomy and appendicectomy is a safe, feasible and cost effective procedure. Keywords: Abdominal hysterectomy, Appendicectomy, Cholecystectomy